Physician Burnout Quality of Life/ Wellness Resource Pilot Program - Harvey, Dr. Felicia (Jour Med Resh and Health Sci, 2020)
Burnout is a syndrome of emotional exhaustion, depersonalization, and a sense of low personal accomplishment that leads to decreased effectiveness at work (American Journal of Medicine, 2003). Despite the efforts to combat burnout, the number of U.S. physicians who experience burnout rose from 45 percent to over 50 percent between 2011 and 2014 (National Center for Biotechnology Information, 2015). The purpose of this quality improvement evidence-based capstone project was to determine whether a physician wellness pilot program can reduce and or eliminate burnout and stress for practicing physicians at an acute care healthcare institution in the Chicago metropolitan area. The capstone project consisted of a pre-intervention survey, an intervention and a post intervention survey. The participants targeted for this evidence-based project were practicing physicians in Illinois that span across all specialty groups. The physician burnout wellness pilot program was implemented during a two-week period of time during which participants were provided with resources to reduce and or eliminate symptoms of burnout. The implementation of the physician wellness pilot program capstone project showed the physicians at this organization were less stressed and more satisfied with their job at (0.555) percent compared to pre intervention survey results that faired (0.77) and that of the national average of (0.80). Additionally, the post intervention survey results showed the physicians at this organization are experiencing a lower level of burnout (0.44) percent compared to pre intervention survey results that faired (0.53), but a higher level of burnout compared to the national average (0.29). Physician burnout is an epidemic that requires immediate attention because it not only effects the physicians, but it effects the healthcare system. As such, regardless of the specialty and demographics of the physicians, organizations and physicians alike must do their part in assessing if burnout exists. The findings showed the importance of physicians being able to recognize the warning signs of burnout, encourage them to seek help when they are stressed, and take active steps towards ridding or reducing burnout. The findings were compatible with evidence-based research that supports building physician resilience by way of the development of a wellness program.